2012
DOI: 10.1159/000339161
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Aspects, Survival Rate, and Predisposing Risk Factors in Patients with Fournier’s Gangrene and Necrotizing Soft Tissue Infections: Evaluation of Clinical Outcome of 55 Patients

Abstract: Objective: To determine predisposing or prognostic factors and mortality rates of patients with Fournier’s gangrene compared to other necrotizing soft tissue infections (NSTI). Material and Methods: Data of 55 intensive care patients (1981–2010) with NSTI were evaluated. Data were collected prospectively. Results: 43.4% of the patients were in septic condition and 27.3% were hemodynamically unstable. Half of the patients showed predisposing factors (52.7%). The lower extremity (63.2%), abdomen (30.9%), and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 49 publications
10
92
3
3
Order By: Relevance
“…Median debridement count was three (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Majority of the debridements were performed under spinoepidural anesthesia; however, twenty-seven patients (22.5%) required general anesthesia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Median debridement count was three (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Majority of the debridements were performed under spinoepidural anesthesia; however, twenty-seven patients (22.5%) required general anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies showing DM as a risk factor for patients with FG. [1,3,6,7] Nevertheless, there are also some studies where DM has been reported as one of the most frequent comorbidities in patients with FG although not influencing outcomes. [8][9][10][11]16,19] Although it was the most common co-morbidity among all patients, DM was not determined as a risk factor for mortality (p=0.429).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Результаты патоморфологических исследований при ГФ представлены в немногочисленных публика-циях в виде данных биопсий и интраоперационных ис-следований [1,6,9,57,58,72,77,81,83,100,113,118]. Выделяют ранние и поздние патоморфологические изменения при ГФ: в сроки 0 -4 суток (в среднем, в течение первых 24 часов) и в сроки свыше 4 суток от начала заболевания, соответственно [5,118].…”
Section: гангрена фурнье (гф)unclassified
“…Cроки госпитализации варьируют от 2 до 278 койко/дней (в среднем, для выживших пациентов -34,8 ± 18,8 койко/дней, для умерших -61,6 ± 38,9 койко/ дней) [83,113]. Более чем в 65% случаев средние сроки госпитализации превышают 20 койко/дней.…”
Section: гангрена фурнье (гф)unclassified